EFEKTIVITAS VARIASI UMPAN PADA FLY TRAP DALAM PENGENDALIAN KEPADATAN LALAT - Savitriani, Shela; Maftukhah, Nur Afni (Poltekkes Kemenkes Tanjung Karang, 2021)
Flies are the main vector of gastrointestinal infections, so it must control them. Flytraps are one of the fly control methods that are considered the few risk to environmental health. This study aims to determine the effectiveness of flytraps decoy variations in chikens farm. The study used a completely randomized design (CRD), during February-April 2019. Two types of bait (shrimp and fish gills) were used from traditional market waste and placed in the flytrap (size 50cm x 50cm x 50cm). All trapped flies were counted using a tally counter two times (every 60 minutes). Experiments were carried out with five replication for each type of bait. The results showed that the total number of flies caught using fish gill bait was more (363) than shrimp (317). In the first 60 minutes, shrimp bait attracts as many as 22.8 flies (SD = 1.3) and 40.6 fish (SD = 3.6) in the second 60 minutes. Gill bait of fish attracted 25.4 individuals (SD = 0.9), and 47.2 individuals (SD = 2.6). The time variable shows the effect on the number of flies caught; it's related to decomposition time. The characteristics of fish gills high in water, protein, and blood are thought to cause interest in flies. The use of flytraps with fish gill bait is more effective than shrimp bait to apply it.Â